How sport participation affects older adults’ health—chain mediation based on intergenerational support and digital divide - Zheng, Jun-yi; Li, Zong-wei; Liu, Meng-ding; Sun, Mei (Frontiers in Public Health, 2025)
IntroductionSports participation is increasingly recognized as a key factor in promoting public health and addressing the challenges of population aging. However, the mechanisms linking sports participation to health outcomes, particularly through social and technological pathways, remain underexplored in China. This study aims to examine the direct and indirect effects of sports participation on older adults’ health, with a focus on the mediating roles of intergenerational support and the digital divide.MethodsUsing data from the 2017 China General Social Survey (CGSS), a representative national dataset, we conducted regression analyses, path analysis, and bootstrap mediation tests. Variables included sports participation, intergenerational support, digital divide, and self-rated health, with controls for demographic and socioeconomic factors.ResultsSports participation significantly improved older adults’ health both directly and indirectly. Mediation analyses revealed three distinct pathways: (1) intergenerational support, (2) digital divide, and (3) a chain mediation effect whereby intergenerational support facilitated digital adaptation, which further enhanced health. The argument that sports participation is beneficial to health persists, although contextual factors such as urbanization and income levels may influence the extent of these benefits.DiscussionThese findings highlight the importance of sports participation not only as a health-enhancing behavior but also as a catalyst for intergenerational interaction and digital inclusion. Policy efforts should strengthen family-based support systems and promote digital adaptation programs for older populations to maximize the health returns of sports participation.